PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021–2025 - Inka Bella Novratiwi; Lusiana; Silvia Sari (STKIP Subang, 2026)
This study aims to determine the effect of capital structure and profitability on firm value with dividend policy as an intervening variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2025 period. This quantitative study uses secondary data obtained from published financial statements. The population consisted of all food and beverage manufacturing companies listed on the IDX during the study period. Samples were selected using purposive sampling, resulting in 23 companies observed over five years. Data were analyzed using multiple linear regression with the assistance of SPSS 26. The results show that capital structure has no significant effect on dividend policy, while profitability has a significant effect on dividend policy. Capital structure and profitability have significant effects on firm value, and dividend policy has a significant effect on firm value. Dividend policy does not mediate the effect of capital structure or profitability on firm value